Grönland och Folketinget : En postkolonial textanalys av grönländska och danska ledamöters uttalanden i Folketinget 1960-1962 - Jönsson, Isak; Elmblad, Jonathan (Linnéuniversitetet, Institutionen för kulturvetenskaper (KV), 2022)
This is a study of Greenlandic and Danish members of parliament's statements in Folketinget between 1960-1962. The study aims to see in which matters the Greenlandic members presented their statements, as well as what can be discerned from the Greenlandic and Danish members’ statements about the formers possibilities to change Greenland’s political situation.The study will also examine the statements made from a postcolonial viewpoint to see if they overlap with the theory. The study shows that the statements made by both the Danish and Greenlandic members of Folketinget overlap with the postcolonial theory several times. Edward Said, Franz Fanon and Michel Foucoults theories can all be traced within their statements. Foremost, Homi Bhabha and what he described as colonial mimicry is found on several occasions. The Greenlandic members of Folketinget made staments in a variety of political areas, both about specific issues on Greenland itself as well as how to change the asymmetrical relationship between Greenland and Denmark. Their possibilities to alter Greenland’s political situation was greatly hindered seeing as the Greenlandic members of Folketinget could not partake on the same terms as their danish collegues. Greenland also lacked any real political power in foreign politics, and therefore any tangible political voice when negotiating international treaties.